Pengaruh Hubungan Kerja Antar Pegawai Dan Kompensasi Terhadap Kinerja Pegawai Pada Kecamatan Cibinong - Muhammad Hafiz Talla Munawar; Lies Putriana (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE INFLUENCE OF WORKPLACE INTERPERSONAL RELATIONSHIPS AND COMPENSATION ON EMPLOYEE PERFORMANCE AT THE CIBINONG DISTRICT OFFICE This study aims to analyze the effect of interpersonal work relationships and compensation on employee performance at the Cibinong District Office using a quantitative approach through a survey method and questionnaires distributed to employees as respondents. The independent variables in this study are interpersonal work relationships (X₁) and compensation (X₂), while the dependent variable is employee performance (Y). The results show that interpersonal work relationships and compensation, both partially and simultaneously, have a positive and significant effect on employee performance, indicating that better work relationships and more appropriate compensation systems will improve employee performance. This study is expected to provide consideration for government institutions in improving employee performance through better work relationships and compensation systems.